Lista Soni Wajselfisz [Karin Ohry Lista Soni; Agnieszka Haska, „Setki znajomych osób”. Lista z Bergen-Belsen] - Ohry-Kossoy, Karin; Haska, Agnieszka (Zagłada Żydów. Studia i Materiały, 2016)
Sonia Wajselfisz (1911–1999) in 1943 was deported from the Warsaw ghetto to the Bergen-Belsen concentration camp; thanks to the so-called Palestinian certificate obtained through the Hotel Polski, people managed to survive the war. Many people in the hotel at Długa 29 Street bought documents issued by South American countries, were not so lucky; on 21 October 1943, 17 May, and 23 May 1944 they were transported to Auschwitz and died there. After the war, Sonia wrote down the names she could recall; the list, found after many years, is a unique document, so one can identify at least part of more than two hundred people from these transports. The article presents a biography of Sonia, and an analysis of the document she drew up.